A population division based multi-task optimization algorithm for solving multiple-team formation problem based on Tiki-Taka optimization algorithm - Ahmmed, Mohammad Badal; Kamal Z., Zamli (2022)
The Team Formation Problem (TFP) has recently gained popularity in Operation Research (OR) . The challenge of finding the lowest or maximum values from a massive pool of solutions is called optimization. Often, meta-heuristic algorithms are chosen to solve optimization issues because they are fast and use few resources. Recent literature research has focused on a new optimization issue termed multi-task optimization (MTO). This article updates our ongoing efforts to address the MTO issue. Specifically, our research examines the use of Tiki-Taka, a football-inspired meta-heuristic algorithm, to solve the MTO issue by adopting a partitioned population method. We use UMP Experts dataset as a case study to optimize team connection costs. Our study proved that TTA could solve MTO Team Formation Problem effectively.